Meningkatkan Pemahaman Tari Tradisional dengan Model Problem Based Learning untuk Projek Penguatan Profil Pelajar Pancasila Tema Kearifan Lokal pada Pelajaran Seni Tari Kelas XI - Mairani, Pemilasari W.; Mardiayanah (Jurnal Pendidikan Tari, 2023)
This research aims to increase students’ comprehension towards traditional dances by analyzing the learning process and outcomes in applying Problem Based Learning as a project to strengthen the profile of Pancasila students in the theme of local wisdom in the Dance Class of Grade XI. The research is carried out due to the problems of student’s incomprehensibility towards traditional dances resulted in the difficulties in creating Creative Dance that is based on traditional dances, which becomes one of the learning objectives Phase-F of Emancipated Curriculum. The classroom action research from Kemis &McTaggard was employed in this research and is conducted in two cycles. Each cycle has four stages, namely planning, action, observation and reflection. This research was conducted from June to September 2023 at SMA Negeri 92 Jakarta, through face-to-face learning. The data were collected through d from scores of objective tests, group discussions and papers, collaborator interviews, student interviews, observations by collaborators, observations by students, and documentation. The results of this research show the average pretest score is 40, the average score in cycle 1 is 72 and the average score in cycle 2 is 88. The learning outcomes have increased by 20% compared to the pretest result in cycle 1. There is an increase of 40% of the result in cycle 2 compared to the result in cycle 1. In conclusion, the application of Problem based Learning model can increase students’ comprehension towards traditional dances for students of grade XI as a project of strengthening Pancasila students’ profile in the theme of local wisdom, that is shown by the increasing of academic outcomes.